Prescrição de fármacos inapropriados em idosos hospitalizados: análise da mortalidade e sobrevida - Flores, Thamara Graziela (2023)
Introduction: Elderly people (>60 years old) have a high prevalence of chronic noncommunicable diseases (DCNTs), often managed through the daily use of four or more drugs (polypharmacy). Furthermore, they may present biogerontological changes that affect the pharmacodynamics and pharmacokinetics of drugs. These situations increase the risk of adverse effects (especially geriatric syndromes), hospitalization, institutionalization and death. Therefore, several drugs are considered “potentially inappropriate medications” (MPIS) for the elderly, and these are prescribed daily in the elderly’s routine. However, the impact of the use of these drugs when used prior to hospitalization still needs to be clarified. Objective: To investigate the hospitalization profile and identify the impact of the use of inappropriate drugs prior to hospitalization on in-hospital mortality in the elderly. Methodology: Two complementary studies will be conducted. Study 1: It sought to evaluate the profile of elderly people upon admission, hospital evolution and outcome, as well as verify the association of the admission profile with the hospitalization outcome. A prospective cohort study was conducted. The variables analyzed for hospital admission were the sociodemographic profile and clinical-functional profile, as well as the evolution variables, the length of hospital stay and complications, and, as an outcome, hospital discharge or death. Study 2: approved by the Research Ethics Committee (CEP-UFSM, CAEE 48212915.50000.5346). It involved an epidemiological, prospective observational investigation in elderly people who sought emergency care and were hospitalized for various causes. Data were obtained through a structured interview that included instruments related to socioeconomic, cultural, lifestyle, health and previous daily use of MPISs and other drugs. Survival assessment was carried out up to 30 days after hospital discharge. Information on the clinical evolution of geriatric syndromes and survival was obtained via medical records. The drugs were pharmacologically categorized according to their action on the systems: nervous, cardiovascular, digestive, endocrine and osteo-muscular. The elderly were then grouped as MPIS users and non-users (control). The evolution of geriatric complications and the survival of the elderly were statistically analyzed using univariate tests and multivariate Cox regression. Results: In study 1, 493 elderly people were evaluated, with the majority of young elderly people, who lived alone, admitted to the hospital due to neoplasia. There was a positive association between death and age, Delirium, Charlson Comorbidity Index, Senior Risk Index, Frailty and calf circumference values. It was found that the elderly population that enters hospital emergency rooms presents multimorbidities, functional declines, frailty and greater exposure to adverse events during hospitalization, including death. In study 2, 318 patients aged ≥ 65 years were evaluated. The medications prescribed by these patients were recorded and the use of MPIS-ph was identified by the Brazilian consensus-based analysis of MPIS use. The impact of the use of MPIS-ph on the survival of hospitalized elderly people was determined through multivariate Cox regression analysis. Conclusions: The functional clinical profile, as well as pharmacological prescriptions, must be analyzed when creating care plans for elderly people entering in emergencies, as there are several variables that affect their outcomes.